Procedings of the British Machine Vision Conference 1995 1995
DOI: 10.5244/c.9.40
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and Recognising Hand Gestures using Statistical Shape Models.

Abstract: Hand gesture recognition from video images is of considerable interest as a means of providing simple and intuitive man-machine interfaces. Possible applications range from replacing the mouse as a pointing device to virtual reality and communication with the deaf. We describe an approach to tracking a hand in an image sequence and recognising, in each video frame, which of five gestures it has adopted. A statistically based Point Distribution Model (PDM) is used to provide a compact parameterised description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Research into methods for capturing signing movements directly from video has been reported e.g. [1]. This approach is highly desirable as it obviates the need to record signs by attaching motion sensors to a human, with the attendant problems of invasiveness, motion restriction, calibration, sensor fusion etc.…”
Section: The Signing Avatar Tessamentioning
confidence: 99%
“…Research into methods for capturing signing movements directly from video has been reported e.g. [1]. This approach is highly desirable as it obviates the need to record signs by attaching motion sensors to a human, with the attendant problems of invasiveness, motion restriction, calibration, sensor fusion etc.…”
Section: The Signing Avatar Tessamentioning
confidence: 99%
“…Analysis times are quoted for a SunSparc 20 which operates at 44 m£ops. Other examples of practical applications include analysis of: industrial inspection images (Hunter et al 1994), hand gestures (Ahmad et al 1995), echocardiograms , mammograms (Ellis 1997), surveillance images (Baumberg & Hogg 1994). The method extends to 3D and has been used to interpret 3D MR images of the brain (Hill et al 1993) and knee cartilage (Solloway et al 1996).…”
Section: Pr Ac T Ic a L A Ppl Ic At Ion S Of Ac T I V E S H A Pe Modementioning
confidence: 99%
“…Next, we use this shape information to warp the face image and extract the shape-free patch, which we approximate using the grey-level model to give b grey . Together b shape and b grey provide a complete description from which the image can be reconstructed (Lanitis et al 1995). The dimensionality of the model can be further reduced by modelling the combination of b shape and b grey in a further PCA model which we have termed a`combined appearance model' (Edwards et al 1996).…”
Section: Mode L L I Ng G Loba L G R Ey-l Ev E L a Ppe A R A Nc E : mentioning
confidence: 99%
See 1 more Smart Citation
“…Processing color-image with a skin-color model and its labeling are used to extract a hand image. Its trajectory is obtained by using the modified BMA (block matching algorithm) from each frame of a sequence of an input image [6] [7] [8]. When this trajectory is analyzed to recognize a gesture according to the predefined window-management rules, the gesture-recognition technique is used to control the display by the window manager [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%